Galician identity in Buenos Aires (1900-1960) - Farias, Ruy (Madrygal. Revista de Estudios Gallegos, 2011)
Argentina was the most important migratory destination for Galicians between the beginning of the 20th century and 1960. This work seeks to shed light on the ways Galician identity was preserved in the context of the new social environment. In order to do so, I will analyze the ways in which the protagonists of this experience preserved, modified, or lost their mother tongue, culinary culture and socializing practices.
Keywords: Galician migration; 20th century; Argentina; identity; integration.